Onset of Skin, Gut, and Genitourinary Prodromal Parkinson's Disease: A Study of 1.5 Million Veterans. Issue 9 (3rd May 2021) - Scott, Gregory D.; Lim, Miranda M.; Drake, Matthew G.; Woltjer, Randy; Quinn, Joseph F.
ABSTRACT: Background: Prodromal Parkinson's disease of skin, genitourinary, and gastrointestinal systems offers a unique window for understanding early disease pathogenesis and developing disease modifying treatments. However, prior studies are limited by incomplete timing information, small sample size, and lack of adjustment for known confounders. Verifying prodromal timing and identifying new disorders in these accessible organs is critically important given their broad use. Objective: We aimed to measure onset timing for gastrointestinal, genitourinary, and skin disorders in a large, nationwide clinically characterized cohort of 1.5 million participants. Methods: Patients with Parkinson's disease (n = 303, 693) were identified using diagnostic codes in the medical records database of the United States Veterans Affairs healthcare system and were compared 4:1 with matched controls. Disorder prevalence and estimated onset times were assessed for 20 years preceding diagnosis. Results: The earliest significantly increased prodromal disorders were gastroesophageal reflux, sexual dysfunction, and esophageal dyskinesia at 17, 16, and 15 years before diagnosis. Estimated onset times for each disorder occurred 5.5 ± 3.4 years before the first measured increase. The earliest estimated onset times were smell/taste, upper gastrointestinal tract, and sexual dysfunction at 20.9, 20.6, and 20.1 years before diagnosis. Onset times for constipation and urinary dysfunction were notably longer by 7 and 9 years compared to prior studies in sleep disorder patients. Dermatophytosis and prostatic hypertrophy were identified as new high prevalence prodromal disorders. Conclusions: Gastrointestinal, genitourinary, and skin disorders manifest decades before diagnosis of Parkinson's disease, reiterating their potential as sites for developing early diagnostic testing and understanding pathogenesis. Abstract : Gastrointestinal, genitourinary, and skin disorders were measured in prodromal Parkinson's disease spanning 20 years in 1.5 million participants. The earliest onset times were smell/taste, upper gastrointestinal tract, and sexual dysfunction at 20.9, 20.6, and 20.1 years before diagnosis. Dermatophytosis and prostatic hypertrophy were identified as new high prevalence prodromal disorders. © 2021 International Parkinson and Movement Disorder Society